2006
DOI: 10.1038/labinvest.3700440
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation induces inflammation, lung injury, and extra-pulmonary organ dysfunction in experimental pneumonia

Abstract: Mechanical ventilation (MV) is frequently employed for the management of critically ill patients with respiratory failure. A major complication of mechanical ventilation (MV) is the development of ventilator-associated pneumonia (VAP), in which Staphylococcus aureus is a prominent pathogen. Moreover, previous studies suggest that MV may be an important cofactor in the development of acute lung injury (ALI) and the acute respiratory distress syndrome (ARDS). S. aureus pulmonary infection was induced in spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 48 publications
4
83
0
2
Order By: Relevance
“…Enhanced lung injury is also seen with mechanical ventilation and Staphylococcus aureus pneumonia. The combination of ventilation and bacterial infection also augmented the injury of nonpulmonary organs, suggesting that mechanical ventilation exacerbates systemic inflammatory responses to bacteria and contributes to the pathogenesis of the multiple organ dysfunction syndrome [45].…”
Section: Epithelial Cell Responses To Mechanical Stretchmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced lung injury is also seen with mechanical ventilation and Staphylococcus aureus pneumonia. The combination of ventilation and bacterial infection also augmented the injury of nonpulmonary organs, suggesting that mechanical ventilation exacerbates systemic inflammatory responses to bacteria and contributes to the pathogenesis of the multiple organ dysfunction syndrome [45].…”
Section: Epithelial Cell Responses To Mechanical Stretchmentioning
confidence: 99%
“…Numerous experimental models of VILI have demonstrated additive or synergistic effects of bacterial products with mechanical ventilation on the development or exacerbation of lung injury [44][45][46][47][48]. Mechanical ventilation using moderate tidal volumes in mice enhanced lipopolysaccharide (LPS)-induced expression of TNF-α, IL-8, growth-related protein-α and monocyte chemoattractant protein (MCP)-1 [44].…”
Section: Epithelial Cell Responses To Mechanical Stretchmentioning
confidence: 99%
“…It is generally accepted that VALI is an excessive, uncontrolled, inflammatory, response within the lung (3). Previous studies have suggested that the release of pro-inflammatory cytokines have a central role in VALI (4,5). Nuclear factor (NF)-κB is required for maximal transcription of various cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-8, and IL-1β (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Such mechanical ventilation is often combined together with an infectious injury to mimic clinical sepsis-induced ALI, [ 12 ], [ 40 ], [ 42 ], [ 63 ] and [ 64 ] although the direct effect of each challenge is difficult to dissociate. We assumed that high-volume ventilation will cause mechanical stress-related injury and hypothesized that the resulting barrier dysfunction [ 65 ] and [ 66 ] will be exacerbated by increases in EC paracellular gap formation in nmMLCK2 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%